MODALITY REALIZATION IN THE TEXTS MARKOBAR IN PABAGAS BORU CEREMONY AS MANDAILING ORAL TRADITION - Asrita . Sari; Sumarsih . .; Rahmad . Husein (LINGUISTIK TERAPAN, 2022)
ABSTRACT Markobar is one of Mandailing oral traditions. Markobar means “speaking”. The study aimed  as certain how modalities were realized in the texts of markobar in pabagas boru ceremony, The study was a qualitative research. the participants comprising 14 positions in markobar  in pabagas boru ceremony, two atobangon (expert of markobar) in Padangsidimpuan were the data source of study. The data of the study were 66 clauses containing modality delivered by participants orally. The theory used was modality theory proposed by Halliday (2004). In addition, the data gained were analyzed based on Miles, Huberman, and Saldana (2014) namely, data collection, data condensation, data display, and conclusion drawing/ verification. Thus, the study showed that there were three categories of modality realization which could be found in markobar in pabagas boru namely, auxiliary verb (32), lexical verb (10), and adverbial phrase (24). Then, modality realized in markobar in pabagas boru ceremony was dominated by auxiliary verbs (48%). Then, the least modal was lexical verb (15%).